2014
DOI: 10.1073/pnas.1408873111
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal effects of value on perceptual acuity and stimulus encoding

Abstract: Cross-modal interactions are very common in perception. An important feature of many perceptual stimuli is their reward-predicting properties, the utilization of which is essential for adaptive behavior. What is unknown is whether reward associations in one sensory modality influence perception of stimuli in another modality. Here we show that auditory stimuli with high-reward associations increase the sensitivity of visual perception, even when sounds and reward associations are both irrelevant for the visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 46 publications
10
69
1
Order By: Relevance
“…Once it was no longer provided, motivational engagement would return to a normal level, or even to a lower level as performance decreased more from training to posttest for the reward group. This finding was contrary to previous evidence that reward influenced visual perception even when the rewards were no longer delivered (Anderson, 2013;Anderson et al, 2011;Failing & Theeuwes, 2014Pooresmaeili et al, 2014;, even after several days (Della Libera & Chelazzi, 2009). These inconsistent findings might be due to the paradigm differences (the proactive paradigm used in the current study and the reactive paradigm used in the above studies ;Braver, 2012;Failing & Theeuwes, 2018;Pessoa, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Once it was no longer provided, motivational engagement would return to a normal level, or even to a lower level as performance decreased more from training to posttest for the reward group. This finding was contrary to previous evidence that reward influenced visual perception even when the rewards were no longer delivered (Anderson, 2013;Anderson et al, 2011;Failing & Theeuwes, 2014Pooresmaeili et al, 2014;, even after several days (Della Libera & Chelazzi, 2009). These inconsistent findings might be due to the paradigm differences (the proactive paradigm used in the current study and the reactive paradigm used in the above studies ;Braver, 2012;Failing & Theeuwes, 2018;Pessoa, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Because there was no previous study using the same paradigm to examine the same issue, we aimed for a sample size of 50 subjects (25 subjects per group) to be comparable with, or larger than the sample sizes of previous studies that examined the influence of rewards on visual perception (Marx & Einhauser, 2015; Pooresmaeili et al, 2014; Seitz, Kim, & Watanabe, 2009; Xue et al, 2015). Based on the sensitivity analysis using G*Power software (Faul, Erdfelder, Buchner, & Lang, 2009), a sample size of 50 would allow us to detect effects ( f ) larger than 0.26 with our design of within‐between interaction of repeated measures, power = 0.95, alpha = 0.05, number of groups = 2, number of measurements = 2, correlation among measurements = 0.5, and nonsphericity correction = 1.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, two studies used auditory reward-learning to form simple stimulus-reward associations; and tested their impact on visual perception23 and attention24. Pooersmaeili and colleagues23 found that high-reward associated sounds increased visual sensitivity in an orientation discrimination task, while Anderson24 found that high-reward associated sounds interfered with the performance in a visual attention task. These seemingly contradicting results indicate that it is currently unknown how exactly the value representations in auditory domain would affect visual processes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the top-down influences on perception, the effect of reward is particularly important to motivate an agent, facilitate learning, and help the agent to behave adaptively given the limited capacity of both sensory and motor systems. It has been shown that reward acts to modulate selective attention when the subject's performance was directly linked to the monetary reward (Small et al, 2005;Mohanty et al, 2008;Engelmann et al, 2009), even when the monetary reward was no longer task-relevant (Libera and Chelazzi, 2006;Hickey and van Zoest, 2012;Pooresmaeili et al, 2014;Asutay and Västfjäll, 2016;Luque et al, 2017). Rewards may act as guiding signals for learning and optimizing specific attentional operations (Chelazzi et al, 2013a), and not only can reward increase the salience of associated stimuli (Hickey and van Zoest, 2012), but also enhance the suppression of the distractors (Della Libera and Chelazzi, 2009), change the priority maps of space (Chelazzi et al, 2014), and reduce the intrinsic neural noise in the motor and cognitive control (Manohar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%